Kontakty interpersonalne staropolskich podróżników stanu duchownego - Rok, Bogdan (Saeculum Christianum. Pismo Historyczne, 2018)
The text presents different types of interpersonal contacts in the course of the journey based on Polish clergymen’s travel reports from the 18th century. The clergy establish numerous contacts primarily with other encountered travelers of their state. Also, information about meetings with peregrines and people on subsequent stages of the journey can be found. Interesting, contacts include Poles and important people of that time. It is important to emphasize the assertiveness of clergy travelers and their openness towards representatives of foreign nations.